Validation of a Terminally Amino Functionalized Tetra‐Alkyl Sn(IV) Precursor in Metal–Organic Chemical Vapor Deposition of SnO2 Thin Films: Study of Film Growth Characteristics, Optical, and Electrical Properties. Issue 1 (25th November 2018) - Zanders, David; Ciftyurek, Engin; Hoppe, Christian; de los Arcos, Teresa; Kostka, Aleksander; Rogalla, Detlef; Grundmeier, Guido; Schierbaum, Klaus Dieter; Devi, Anjana
Abstract: Tin(IV) oxide is a promising semiconductor material with leading‐edge properties toward chemical sensing and other applications. For the growth of its thin films, metal–organic chemical vapor deposition (MOCVD) routes are advantageous due to their excellent scalability and potential to tune processing temperatures by careful choice of the reactants. Herein, a new and highly efficient MOCVD process for the deposition of tin(IV) oxide thin films employing a terminally amino alkyl substituted tin(IV) tetra‐alkyl compound is reported for the first time. The liquid precursor, tetrakis‐[3‐( N, N ‐dimethylamino)propyl] tin(IV), [Sn(DMP)4 ], is thermally characterized in terms of stability and vapor pressure, yielding highly pure, polycrystalline tin(IV) oxide thin films with tunable structural and morphological features in the presence of oxygen. Detailed X‐ray photoelectron spectroscopy (XPS) analysis reveals the presence of oxygen vacancies and high amounts of chemisorbed oxygen species. Based on these promising features, the MOCVD process is optimized toward downscaling the thickness of tin(IV) oxide films from 25 to 50 nm to study the impact of incipient surface morphological changes occurring after initial thin‐film formation on the electrical properties as investigated by van der Pauw (vdP) resistivity measurements. Optical bandgaps of thin films with varying thicknesses are estimated using ultraviolet–visible (UV–vis) spectroscopy. Abstract : A terminally amino functionalized tetra‐alkyl Sn(IV) precursor is synthesized and thoroughly characterized. The favorable physico‐chemical properties facilitated the chemical vapor deposition (CVD) of high‐purity SnO2 thin films. In a combinatorial approach, the profound impact of surface morphology and roughness on the electrical properties of SnO2 films with thicknesses of 50 nm and below is investigated.